What is the Text Encoding Initiative? - Lou Burnard (OpenEdition Press, 2014)
The Text Encoding Initiative (TEI) Guidelines have long been regarded as the de facto standard for the preparation of digital textual resources in the scholarly research community. For the beginner, they offer a daunting range of possibilities, reflecting the huge range of potential applications for text encoding, from traditional scholarly editions, to language corpora, historical lexicons, digital archives and beyond. Drawing on many examples of TEI-encoded text from a variety of research ...
Keywords: digital editing; XML; digital humanities; TEI; text encoding